Analysis Of The Influence Of Brand Image, Price, Service Quality On Purchasing Decisions By Mediating Customer Satisfaction On Drinks At Coffee Shops - Cindy Cindy; Immanuel Zai (Journal Research of Social Science, Economics, and Management, 2024)
The purpose of this study is to determine and analyze the influence of brand image, price, and product quality on purchasing decisions by mediating customer satisfaction on drinks at Batam City coffee shops with a number of respondents as many as 210 people. This research is basic research and is quantitative. Data collection techniques go through literature studies and field studies using questionnaires. Data analysis techniques are launched by managing data statistically using the help of smart PLS applications. Through the processing of data that has been done, it is found that brand image does not have a significant effect on purchasing decisions. Price has a significant influence on purchasing decisions. Service quality has a significant influence on purchasing decisions. Customer satisfaction does not have a significant effect on purchasing decisions. Brand image has a significant effect on customer satisfaction. Price has a significant effect on customer satisfaction. Service quality does not have a significant effect on customer satisfaction. Brand image cannot influence purchasing decisions mediated by customer satisfaction. Price cannot influence purchasing decisions mediated by customer satisfaction. Service quality cannot influence purchasing decisions mediated by customer satisfaction.